Soil Aggregation in Relation to Land Use and Seasons - Kolay, A.K.; Sinha, H.; Sinha, B.P. (Journal of Soil and Water Conservation, 2022)
The resent results of Singh and Chatterjee ( 1966 ) and Mahant and Singh ( 1969 ) have indicated that aggregation of Kanke (Ranchi ) soil may increase or decrease due to cultivation depending on the nature of crops grown. Soil aggregation is also liable to change with seasons (Alderfer 1946). According to Combean and Quantin ( 1963 ), the structural stability of tropical soils was the lowest during the months of heaviest rainfall which improved rapidly during the first month of dry season and more slowly in the subsequent months until the onset of rains. In view of varied effects on soil aggregation due to culti- vation and lack of informations on seasonal effects, the present investigation was taken up to determine the effect of various land use on soil aggregation of an upland red loam of Ranchi in different seasons.